Cytokine Signaling and Matrix Remodeling Pathways Associated with Cardiac Sarcoidosis Disease Activity Defined Using FDG PET Imaging - Young, Bryan D.; Moreland, Hannah; Oatmen, Kelsie E.; Freeburg, Lisa A.; Shahab, Zartashia; Herzog, Erica; Miller, Edward J.; Spinale, Francis G. (International Heart Journal, 2021)
While cardiac imaging has improved the diagnosis and risk assessment for cardiac sarcoidosis (CS), treatment regimens have consisted of generalized heart failure therapies and non-specific anti-inflammatory regimens. The overall goal of this study was to perform high-sensitivity plasma profiling of specific inflammatory pathways in patients with sarcoidosis and with CS.Specific inflammatory/proteolytic cascades were upregulated in sarcoidosis patients, and certain profiles emerged for CS patients.Plasma samples were collected from patients with biopsy-confirmed sarcoidosis undergoing F-18 fluorodeoxyglucose positron emission tomography (n = 47) and compared to those of referent control subjects (n = 6). Using a high-sensitivity, automated multiplex array, cytokines, soluble cytokine receptor profiles (an index of cytokine activation), as well as matrix metalloproteinase (MMP), and endogenous MMP inhibitors (TIMPs) were examined.The plasma tumor necrosis factor (TNF) and soluble TNF receptors sCD30 and sTNFRI were increased using sarcoidosis, and sTNFRII increased in CS patients (n = 18). The soluble interleukin sIL-2R and vascular endothelial growth factor receptors (sVEGFR2 and sVEGFR3) increased to the greatest degree in CS patients. When computed as a function of referent control values, the majority of soluble cytokine receptors increased in both sarcoidosis and CS groups. Plasma MMP-9 levels increased in sarcoidosis but not in the CS subset. Plasma TIMP levels declined in both groups.The findings from this study were the identification of increased activation of a cluster of soluble cytokine receptors, which augment not only inflammatory cell maturation but also transmigration in patients with sarcoidosis and patients with cardiac involvement.